Zirconium metal oxide nano-cluster photoresist material modified by fluorine-containing aromatic acid ligand as well as preparation method and application of zirconium metal oxide nano-cluster photoresist material
By introducing fluorine-containing aromatic acid ligands into zirconium metal oxide nanocluster photoresist, the problem of insufficient resolution and sensitivity in existing photoresist in extreme ultraviolet lithography technology is solved, and the photolithography pattern with high resolution and low linear edge roughness is achieved, which improves the overall performance of the photoresist.
Patent Information
- Application Number
- CN202411531802.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-10-30
AI Technical Summary
In the extreme ultraviolet photoresist, it is difficult to form high-resolution, low-line edge roughness photolithography patterns in existing metal oxide nanocluster photoresist, and its sensitivity is not sufficient to meet the needs of high-integration chips.
By introducing a partial fluorine-containing aromatic acid ligand into the zirconium metal oxide nanoclusters, a zirconium metal oxide nanocluster with mixed ligands was prepared by ligand exchange method.
It significantly improves the resolution of the lithographic pattern and the roughness of the line edge, enhances the sensitivity of the photoresist, and is suitable for ultraviolet lithography, electron beam lithography and extreme ultraviolet lithography technologies.
Smart Images

Figure BDA0005110643270000021 
Figure BDA0005110643270000031 
Figure BDA0005110643270000041
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photoresist technology materials, and specifically relates to a zirconium metal oxide nanocluster photoresist material modified by a fluorine-containing aromatic acid ligand, and a preparation method and application thereof. Background Art
[0002] As the world enters the digital age, computers, smart electronic products and the Internet are increasingly becoming the center of life and production, which has led to increasing performance requirements for digital processors and memory, which means that the integration of electronic components is becoming increasingly higher.
[0003] The line width limit and precision of photolithography directly determine the integration, reliability and cost of integrated circuits. Photoresist is the most critical material in the photolithography process. By coating the photoresist on the surface of the silicon wafer and then irradiating it with light of a specific wavelength, the photoresist will undergo chemical changes according to the exposure of the light, and finally form the desired pattern through development. The resolution of the photoresist determines the minimum feature size of the chip that can be manufactured. High-resolution photoresist can achieve finer patterns, thereby improving the integration and performance of the chip.
[0004] Extreme ultraviolet lithography (EUVL) is currently the most advanced lithography technology in the world. The low photon utilization efficiency of its light source severely limits the production capacity of the EUVL system. Therefore, the development of more sensitive EUV resists has become an urgent need in the current semiconductor industry. In recent years, a variety of new metal-containing photoresists have been developed, among which metal oxide clusters are favored by researchers due to their small and uniform molecular size and elements with high EUV absorption cross-sections.
[0005] The development of EUV photoresists has been limited by three factors: resolution, line edge roughness, and photosensitivity. These three factors are mutually restrictive. The metal oxide nanocluster photoresists currently studied are mainly concentrated on a single carboxylic acid ligand, among which methacrylic acid ligands are the main ones. This type of metal oxide nanocluster photoresist with methacrylic acid ligand has a high sensitivity when forming a photolithographic pattern, but its pattern resolution is low and it cannot form a pattern with higher resolution.
[0006] Chinese patent document CN 111948904 A discloses a photoresist composition and a preparation method thereof, comprising: a metal oxide nanocluster, wherein the metal oxide nanocluster comprises a metal oxide core and an organic ligand coordinated with the metal oxide core, and the molecular formula thereof is M x O y (OH) m L n, M is a metal element, L is the organic ligand, and is an organic group containing a double bond, 4≤x≤8, 2≤y≤8, 0≤m<4, 12≤n≤16; a photoacid generator; a free radical quencher; and a solvent. M can be selected from any one of zirconium, titanium and hafnium, preferably zirconium. The metal oxide nanoclusters can be zirconium oxide, titanium oxide, or hafnium oxide. The metal oxide nanoclusters have a high light absorption rate, which can effectively improve the energy utilization rate, so that the energy absorbed in the photoresist is higher, and the free radical reaction is more effectively induced, thereby improving the sensitivity. However, the minimum line width feature size of the photolithographic pattern obtained by the invention is 26nm, and the pattern quality is poor, and it is impossible to form a higher quality and higher resolution pattern.
[0007] Therefore, how to form higher quality and higher resolution lithography patterns with minimal impact on the sensitivity of metal oxide clusters is the most urgent problem to be solved. Summary of the invention
[0008] In view of the shortcomings of the prior art, the present invention provides a zirconium metal oxide nanocluster photoresist material modified with a fluorine-containing aromatic acid ligand, and a preparation method and application thereof. The present invention introduces some fluorine-containing aromatic acid ligands into zirconium-based metal oxide nanoclusters by a ligand exchange method to obtain zirconium metal oxide nanoclusters with mixed ligands; the preparation method of the present invention is simple, the raw materials are cheap and easy to obtain, the cost is low, and it is suitable for industrial production. The zirconium metal oxide nanocluster photoresist material modified with a fluorine-containing aromatic acid ligand of the present invention can be applied to ultraviolet lithography, electron beam lithography, and extreme ultraviolet lithography, and the formed lithographic pattern has the advantages of low line edge roughness and high resolution, and has broad application prospects.
[0009] The technical solution of the present invention is as follows:
[0010] A fluorinated aromatic acid ligand-modified zirconium metal oxide nanocluster photoresist material, the general structural formula of which is Zr6O4(OH)4(MAA) x (L) 12-x , wherein x is 0-11, MAA is a methacrylic acid ligand, and L is a fluorine-containing aromatic acid ligand.
[0011] According to the present invention, preferably, the fluorine-containing aromatic acid ligand is a ligand formed by one or two of the following coordination compounds:
[0012]
[0013] According to a preferred embodiment of the present invention, x is 7-11.
[0014] The method for preparing the above-mentioned fluorine-containing aromatic acid ligand-modified zirconium metal oxide nanocluster photoresist material comprises the steps of:
[0015] Zr6O4(OH)4(MAA) 12 The solution is mixed with a fluorine-containing aromatic acid ligand compound solution, and after reaction, rotary evaporation and drying, a zirconium metal oxide nanocluster photoresist material modified with a fluorine-containing aromatic acid ligand is obtained.
[0016] According to the preferred embodiment of the present invention, Zr6O4(OH)4(MAA) 12 The solvent used in the solution is one or a combination of two or more of propylene glycol methyl ether, propylene glycol methyl ether acetate, ethyl lactate, acetone, methanol, ethanol, cyclohexanone, cyclopentanone, tetrahydrofuran, chloroform, n-butanol, dichloromethane or toluene; Zr6O4(OH)4(MAA) 12 The concentration of the solution is 0.01-1 mol / L.
[0017] Preferably according to the present invention, the solvent used for the fluorine-containing aromatic acid ligand compound solution is one or a combination of two or more of propylene glycol methyl ether, propylene glycol methyl ether acetate, ethyl lactate, acetone, methanol, ethanol, cyclohexanone, cyclopentanone, tetrahydrofuran, chloroform, n-butanol, dichloromethane or toluene; the concentration of the fluorine-containing aromatic acid ligand compound solution is 0.01-1 mol / L.
[0018] According to the preferred embodiment of the present invention, Zr6O4(OH)4(MAA) 12 The molar ratio of the fluorine-containing aromatic acid ligand compound is 1:1-5, preferably 1:3-4.2, and more preferably 1:3.
[0019] According to the present invention, preferably, the fluorine-containing aromatic acid ligand compound is selected from one or two of the following:
[0020]
[0021] Preferably according to the present invention, the reaction temperature is room temperature, the reaction time is 5-15 min, and the reaction is carried out under stirring conditions.
[0022] Preferably, according to the present invention, the rotary evaporation temperature is 35-45° C., the rotary evaporation time is 10-20 min, and the drying is vacuum drying at room temperature.
[0023] According to the present invention, Zr6O4(OH)4(MAA) 12 It can be prepared according to the existing method. Preferably, Zr6O4(OH)4(MAA) 12 The preparation method comprises the steps of: mixing the n-propanol solution of zirconium n-propoxide and methacrylic acid uniformly, reacting, standing for crystallization, separating, and drying to obtain Zr6O4(OH)4(MAA) 12 .
[0024] Preferably, the concentration of the zirconium n-propoxide n-propanol solution is 60-80wt%; the molar ratio of zirconium n-propoxide to methacrylic acid is 0.1-0.5:1; the reaction temperature is 60-80°C, the reaction time is 15-20h, and the reaction is carried out under stirring; the crystallization temperature is room temperature, and the crystallization time is 1-3 days.
[0025] A photoresist composition comprises the following components by mass: 1-3 parts of solvent, 0.01-0.5 parts of zirconium metal oxide nanocluster photoresist material modified by fluorine-containing aromatic acid ligands, and 0.005-0.05 parts of photoacid generator.
[0026] According to the present invention, preferably, the solvent is selected from one or a combination of two or more of propylene glycol methyl ether, propylene glycol methyl ether acetate, ethyl lactate, acetone, methanol, ethanol, cyclohexanone, cyclopentanone, tetrahydrofuran, chloroform, n-butanol, dichloromethane, butyl acetate, n-hexane, N-methylpyrrolidone, carbon tetrachloride, γ-butyrolactone, ethylene glycol ethyl ether, isopropanol or toluene.
[0027] According to the present invention, the photoacid generator is preferably selected from 2-(2-(((propylsulfonyl)oxy)imino)thiophene-3(2H)-ylidene)-2-(o-tolyl)acetonitrile (acid generator PAG 103), 2-(2-(((octylsulfonyl)oxy)imino)thiophene-3(2H)-ylidene)-2-(o-tolyl)acetonitrile (acid generator PAG 108), N-hydroxynaphthalimide trifluoromethanesulfonic acid, N-hydroxysulfonic acid succinimide or N-hydroxyphthalimide p-toluenesulfonate, or a combination of two or more thereof.
[0028] The preparation method of the photoresist composition comprises the steps of: fully dispersing the zirconium metal oxide nanocluster photoresist material modified by fluorine-containing aromatic acid ligand and the photoacid generator in a solvent to obtain the photoresist composition.
[0029] Application of the above-mentioned zirconium metal oxide nanocluster photoresist material or photoresist composition modified by fluorine-containing aromatic acid ligand in photolithography technology.
[0030] Taking 4-fluoro-2-methylbenzoic acid organic ligand as an example, the preparation route of zirconium metal oxide nanocluster photoresist material modified by fluorinated aromatic acid ligand is as follows:
[0031]
[0032] The technical features and beneficial effects of the present invention are as follows:
[0033] 1. The present invention is based on zirconium-based metal oxide nanoclusters Zr6O4(OH)4(MAA) 12Part of the fluorine-containing aromatic acid ligands are introduced into the zirconium-based metal oxide nanocluster organic shells, which are initially composed of only methacrylic acid ligands, and the zirconium metal oxide nanocluster photoresist material modified with the fluorine-containing aromatic acid ligands is obtained by ligand exchange. The acid ligand exchange method of the invention has simple process, mild conditions, no need for heating and gas introduction, simple operation steps, cheap and easy-to-obtain raw materials, low cost, good stability of the metal oxygen clusters after acid ligand exchange, high yield, and is suitable for industrial production.
[0034] 2. The present invention introduces fluorine-containing aromatic acid ligands, which stabilize the free radical cations generated after ionization, prevent rapid decarboxylation and cross-linking reactions, significantly improve the contrast of the development, and are conducive to reducing the roughness of the line edge and generating high-resolution patterns, and can achieve finer lines. Since the fluorine element has a strong absorption of extreme ultraviolet light, the problem of reduced reactivity due to the introduction of aromatic ligands is reduced, and the sensitivity of the fluorine-free aromatic ligand metal oxygen cluster is improved.
[0035] 3. There are many types of fluorine-containing aromatic acid ligands, and the physical and chemical properties of metal oxide nanocluster materials synthesized by different ligands are different. The present invention screens specific fluorine-containing aromatic ligands through a large number of experiments, and the obtained photoresist material has the advantages of good solubility, film-forming properties, storage stability, etc. While maintaining a high sensitivity, the resolution is significantly improved compared with the zirconium metal oxide cluster with methyl methacrylate ligand currently studied, and it has the advantage of low line edge roughness. It is suitable for ultraviolet lithography, electron beam lithography, and extreme ultraviolet lithography, and has broad application prospects.
[0036] 4. In the preparation method of the present invention, the selection of solvent type, the selection of fluorinated aromatic acid ligand, Zr6O4(OH)4(MAA) 12 The selection of the ratio of the fluorinated aromatic acid ligand compound and the type of the photoacid generator will affect the quality of the subsequent photolithography pattern. If the above conditions are not suitable, high-resolution patterns cannot be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is the hydrogen nuclear magnetic spectrum of the zirconium-based metal oxide nanoclusters prepared in Comparative Example 1.
[0038] Figure 2 This is the H NMR spectrum of the fluorine-free aromatic acid ligand-modified zirconium metal oxide nanocluster photoresist material prepared in Comparative Example 3.
[0039] Figure 3 This is the H NMR spectrum of the zirconium metal oxide nanocluster photoresist material modified with fluorine-containing aromatic acid ligands prepared in Example 1.
[0040] Figure 4This is the H NMR spectrum of the zirconium metal oxide nanocluster photoresist material modified with fluorine-containing aromatic acid ligands prepared in Example 3.
[0041] Figure 5 It is the thermogravimetric spectrum of the zirconium metal oxide nanocluster photoresist material prepared in comparative example 1, comparative example 3 and embodiment 1 in air atmosphere.
[0042] Figure 6 This is a morphology picture of the zirconium metal oxide nanocluster photoresist film modified with fluorine-containing aromatic acid ligands prepared in Example 5 under an atomic force microscope.
[0043] Figure 7 This is a diagram showing the solubility performance of the zirconium metal oxide nanocluster photoresist material modified with fluorine-containing aromatic acid ligands prepared in Example 1 in different solvents.
[0044] Figure 8 This is the electron beam lithography pattern of the photoresist film prepared in Comparative Example 2.
[0045] Fig. 9 This is the electron beam lithography pattern of the photoresist film prepared in Comparative Example 4.
[0046] Fig.10 This is the electron beam lithography pattern of the photoresist film prepared in Example 5.
[0047] Fig.11 This is the electron beam lithography pattern of the photoresist film prepared in Example 5.
[0048] Fig.12 This is the electron beam lithography pattern of the photoresist film prepared in Example 6.
[0049] Fig.13 This is the electron beam lithography pattern of the photoresist film prepared in Example 7. DETAILED DESCRIPTION
[0050] The present invention is further described below by specific examples, but is not limited thereto. The experimental methods described in the examples are conventional methods unless otherwise specified; the reagents and materials used are commercially available unless otherwise specified.
[0051] Comparative Example 1
[0052] A zirconium-based metal oxide nanocluster Zr6O4(OH)4(MAA) with all methacrylic acid ligands 12 The preparation method comprises the steps of:
[0053] 20 g of 70 wt% zirconium n-propoxide (0.043 mol) n-propanol solution was pre-added to a three-necked flask, and 20 g (0.23 mol) of methacrylic acid solution was added. After pre-stirring for 5 min in an air atmosphere, the mixture was heated to 70°C and reacted for 18 h. After the reaction was completed, the mixture was naturally cooled to room temperature, and crystallized at room temperature for 2 days to obtain single crystals. Colorless crystals were separated and vacuum dried at 25°C for 6 h to obtain a sample of Zr-MAA.
[0054] The nuclear magnetic hydrogen spectrum of the nanoclusters prepared in this comparative example is as follows Figure 1 As shown, A1 and A2 are the characteristic peaks of hydrogen on the methylene group in the carbon-carbon double bond in the methacrylic acid ligand, and B is the characteristic peak of hydrogen on the methyl group in methacrylic acid, which proves the successful synthesis of the target product.
[0055] Comparative Example 2
[0056] A photoresist composition comprises the following components: 2.09 g of propylene glycol methyl ether acetate as a solvent, 0.1 g of a zirconium-based metal oxide nanocluster photoresist material containing all methacrylic acid ligands prepared by the method of comparative example 1, and 0.01 g of N-hydroxynaphthaleneimide trifluoromethanesulfonic acid as a photoacid generator.
[0057] The preparation method of the above-mentioned photoresist composition comprises the following steps:
[0058] To 2.09 g of propylene glycol methyl ether acetate was added 0.1 g of zirconium metal oxide nanoclusters Zr6O4(OH)4(MAA) prepared by the method of Comparative Example 1, which were all methacrylic acid ligands. 12 The photoresist material is added with 0.01 g of N-hydroxynaphthaleneimide trifluoromethanesulfonic acid, stirred evenly at room temperature, and filtered with a 0.22-micron polytetrafluoroethylene filter to obtain the photoresist material.
[0059] The obtained photoresist system was spin-coated on the surface of a two-inch silicon wafer, and the specific process flow was spin-coating, pre-baking, electron beam exposure, and development to obtain a silicon wafer coated with a pattern. The specific process parameters are shown in Table 1 below.
[0060] Table 1
[0061]
[0062] Comparative Example 3
[0063] A method for preparing a fluorine-free aromatic acid ligand-modified zirconium metal oxide nanocluster photoresist material comprises the following steps:
[0064] Take 1.01g (0.000595mol) of zirconium metal oxide nanoclusters Zr-MAA with all methyl methacrylate ligands prepared according to the method of comparative example 1 and 0.218g (0.00178mol) of benzoic acid and dissolve them in 10ml of chloroform respectively. Then, mix and stir the two solutions at room temperature for ten minutes, and then rotary evaporate the solution at 40°C for 15min. The obtained sample is evacuated at room temperature for 30min with a vacuum pump to obtain a white solid powder. The yield is 95.31%. The nuclear magnetic hydrogen spectrum of the nanoclusters prepared in this comparative example is shown as follows: Figure 2 As shown, the successful introduction of the benzoic acid ligand was demonstrated.
[0065] Comparative Example 4
[0066] A photoresist composition comprises the following components: 2.09 g of solvent propylene glycol methyl ether, 0.1 g of fluorine-free aromatic acid ligand-modified zirconium metal oxide nanocluster photoresist material prepared by the method of comparative example 3, and 0.01 g of photoacid generator N-hydroxynaphthaleneimide trifluoromethanesulfonic acid.
[0067] The preparation method of the above-mentioned photoresist composition comprises the following steps:
[0068] To 2.09 g of propylene glycol methyl ether, add 0.1 g of the fluorine-free aromatic acid ligand-modified zirconium metal oxide nanocluster photoresist material prepared by the method of Comparative Example 3, add 0.01 g of N-hydroxynaphthaleneimide trifluoromethanesulfonic acid, stir evenly at room temperature, and filter with a 0.22 μm polytetrafluoroethylene filter to obtain the product.
[0069] The obtained photoresist system was spin-coated on the surface of a two-inch silicon wafer, and the specific process flow was spin-coating, pre-baking, electron beam exposure, and development to obtain a silicon wafer coated with a pattern. The specific process parameters are shown in Table 2 below.
[0070] Table 2
[0071]
[0072] Example 1
[0073] A method for preparing a zirconium metal oxide nanocluster photoresist material modified by a fluorine-containing aromatic acid ligand comprises the following steps:
[0074] 1.01 g (0.000595 mol) of zirconium metal oxide nanoclusters Zr-MAA with all methacrylic acid ligands prepared according to the method of Comparative Example 1 and 0.276 g (0.00179 mol) of 4-fluoro-2-methylbenzoic acid were dissolved in 10 ml of chloroform, and then the two solutions were mixed and stirred at room temperature for ten minutes, and then rotary evaporated at 40° C. for 15 minutes, and the obtained sample was vacuumed at room temperature for 30 minutes using a vacuum pump to obtain a white solid powder. The yield of the obtained sample was 97.88%.
[0075] The H NMR spectrum of the zirconium metal oxide nanocluster photoresist material modified with fluorinated aromatic acid ligands prepared in this example is shown in FIG. Figure 3 As shown, it can be seen from the figure that the 4-fluoro-2-methylbenzoic acid ligand was successfully introduced.
[0076] Example 2
[0077] A method for preparing a zirconium metal oxide nanocluster photoresist material modified by a fluorine-containing aromatic acid ligand comprises the following steps:
[0078] 1.01 g (0.000595 mol) of zirconium metal oxide nanoclusters Zr-MAA containing all methyl methacrylate ligands prepared according to the method of Comparative Example 1 and 0.384 g (0.00249 mol) of 4-fluoro-2-methylbenzoic acid were dissolved in 10 ml of chloroform respectively, and then the two solutions were mixed and stirred at room temperature for ten minutes, and then rotary evaporated at 40° C. for 15 min. The obtained sample was evacuated at room temperature for 30 min using a vacuum pump to obtain a white solid powder.
[0079] Example 3
[0080] A method for preparing a zirconium metal oxide nanocluster photoresist material modified by a fluorine-containing aromatic acid ligand comprises the following steps:
[0081] 1.01 g (0.000595 mol) of zirconium metal oxide nanoclusters Zr-MAA with all methacrylic acid ligands prepared according to the method of Comparative Example 1 and 0.251 g (0.00179 mol) of p-fluorobenzoic acid were dissolved in 10 ml of chloroform, and then the two solutions were mixed and stirred at room temperature for ten minutes, and then rotary evaporated at 40° C. for 15 minutes. The obtained sample was evacuated at room temperature for 30 minutes using a vacuum pump to obtain a white solid powder. The yield of the obtained sample was 94.02%.
[0082] The H NMR spectrum of the zirconium metal oxide nanocluster photoresist material modified with fluorinated aromatic acid ligands prepared in this example is shown in FIG. Figure 4 As shown, it can be seen from the figure that the p-fluorobenzoic acid ligand was successfully introduced.
[0083] Example 4
[0084] A method for preparing a zirconium metal oxide nanocluster photoresist material modified by a fluorine-containing aromatic acid ligand comprises the following steps:
[0085] 1.01 g (0.000595 mol) of zirconium metal oxide nanoclusters Zr-MAA with all methacrylic acid ligands prepared according to the method of Comparative Example 1 and 0.251 g (0.00179 mol) of 2-fluorobenzoic acid were dissolved in 10 ml of chloroform, and then the two solutions were mixed and stirred at room temperature for ten minutes, and then rotary evaporated at 40° C. for 15 minutes. The obtained sample was evacuated at room temperature for 30 minutes using a vacuum pump to obtain a white solid powder. The yield of the obtained sample was 93.15%.
[0086] Example 5
[0087] A photoresist composition comprises the following components: 2.09 g of propylene glycol methyl ether as solvent, 0.1 g of zirconium metal oxide nanocluster photoresist material modified with fluorine-containing aromatic acid ligand prepared by the method of Example 1, and 0.01 g of N-hydroxynaphthaleneimide trifluoromethanesulfonic acid as photoacid generator.
[0088] The preparation method of the above-mentioned photoresist composition comprises the following steps:
[0089] To 2.09 g of propylene glycol methyl ether, add 0.1 g of the fluorinated aromatic acid ligand-modified zirconium metal oxide nanocluster photoresist material prepared by the method of Example 1, add 0.01 g of N-hydroxynaphthaleneimide trifluoromethanesulfonic acid, stir evenly at room temperature, and filter with a 0.22 μm polytetrafluoroethylene filter to obtain the product.
[0090] The obtained photoresist system was spin-coated on the surface of a two-inch silicon wafer, and the specific process flow was spin-coating, pre-baking, electron beam exposure, and development to obtain a silicon wafer coated with a pattern. The specific process parameters are shown in Table 3 below.
[0091] Table 3
[0092]
[0093] Example 6
[0094] A photoresist composition comprises the following components: 2.09 g of propylene glycol methyl ether as solvent, 0.1 g of zirconium metal oxide nanocluster photoresist material modified with fluorine-containing aromatic acid ligand prepared by the method of Example 2, and 0.01 g of N-hydroxynaphthaleneimide trifluoromethanesulfonic acid as photoacid generator.
[0095] The preparation method of the above-mentioned photoresist composition comprises the following steps:
[0096] To 2.09 g of propylene glycol methyl ether, add 0.1 g of the fluorinated aromatic acid ligand-modified zirconium metal oxide nanocluster photoresist material prepared by the method of Example 2, add 0.01 g of N-hydroxynaphthaleneimide trifluoromethanesulfonic acid, stir evenly at room temperature, and filter with a 0.22 μm polytetrafluoroethylene filter to obtain the product.
[0097] The obtained photoresist system was spin-coated on the surface of a two-inch silicon wafer, and the specific process flow was spin-coating, pre-baking, electron beam exposure, and development to obtain a silicon wafer coated with a pattern. The specific process parameters are shown in Table 4 below.
[0098] Table 4
[0099]
[0100] Example 7
[0101] A photoresist composition comprises the following components: 2.09 g of propylene glycol methyl ether as solvent, 0.1 g of zirconium metal oxide nanocluster photoresist material modified with fluorine-containing aromatic acid ligand prepared by the method of Example 3, and 0.01 g of N-hydroxynaphthaleneimide trifluoromethanesulfonic acid as a photoacid generator.
[0102] The preparation method of the above-mentioned photoresist composition comprises the following steps:
[0103] To 2.09 g of propylene glycol methyl ether, add 0.1 g of the fluorinated aromatic acid ligand-modified zirconium metal oxide nanocluster photoresist material prepared by the method of Example 3, add 0.01 g of N-hydroxynaphthaleneimide trifluoromethanesulfonic acid, stir evenly at room temperature, and filter with a 0.22 μm polytetrafluoroethylene filter to obtain the product.
[0104] The obtained photoresist system was spin-coated on the surface of a two-inch silicon wafer, and the specific process flow was spin-coating, pre-baking, electron beam exposure, and development to obtain a silicon wafer coated with a pattern. The specific process parameters are shown in Table 5 below.
[0105] Table 5
[0106]
[0107] Example 8
[0108] A photoresist composition comprises the following components: 2.09 g of propylene glycol methyl ether as solvent, 0.1 g of zirconium metal oxide nanocluster photoresist material modified with fluorine-containing aromatic acid ligand prepared by the method of Example 4, and 0.01 g of N-hydroxynaphthaleneimide trifluoromethanesulfonic acid as photoacid generator.
[0109] The preparation method of the above-mentioned photoresist composition comprises the following steps:
[0110] To 2.09 g of propylene glycol methyl ether, add 0.1 g of the fluorinated aromatic acid ligand-modified zirconium metal oxide nanocluster photoresist material prepared by the method of Example 4, add 0.01 g of N-hydroxynaphthaleneimide trifluoromethanesulfonic acid, stir evenly at room temperature, and filter with a 0.22 μm polytetrafluoroethylene filter to obtain the product.
[0111] The obtained photoresist system was spin-coated on the surface of a two-inch silicon wafer, and the specific process flow was spin-coating, pre-baking, electron beam exposure, and development to obtain a silicon wafer coated with a pattern. The specific process parameters are shown in Table 6 below.
[0112] Table 6
[0113]
[0114] Test Example 1
[0115] The products of Comparative Example 1, Comparative Example 3 and Example 1 were subjected to thermal analysis.
[0116] Thermal analysis (NETZSCH, model STA449F3): In air environment, the temperature was raised from room temperature to 800°C at a rate of 10°C / min. The obtained thermal analysis curve is as follows Figure 5 As shown in the figure, it can be seen that all three samples have good thermal stability, and the thermal stability curve remains unchanged after storage for two months.
[0117] Test Example 2
[0118] In order to evaluate the quality of the photoresist film spin-coated in Example 5, the surface morphology of the photoresist film was collected using an atomic force microscope (AFM) (Shimadzu, model: SPM-9700HT) in non-contact mode, and the collection area was set to 10 μm*10 μm. The surface morphology of the photoresist film of Example 1 observed by AFM is shown in FIG. Figure 6 As shown, the measured root mean square roughness (Rq) of the film is 0.466 nm, indicating that its surface is flat and smooth and the film quality is good.
[0119] Test Example 3
[0120] In order to evaluate the solubility of the fluorinated aromatic acid ligand-modified zirconium metal oxide nanocluster photoresist material synthesized in Example 1, it was dissolved in a variety of solvents including propylene glycol methyl ether acetate, with a solid content of 5%. Figure 7 As shown, the metal oxygen clusters containing fluorinated aromatic acid ligands can be completely dissolved in a variety of solvents, which indicates that the metal oxygen clusters containing fluorinated aromatic acid ligands have good solubility properties.
[0121] Test Example 4
[0122] In order to prove that the fluorine-containing aromatic acid ligand improves the imaging quality of the photoresist, the photoresist film in Comparative Example 2 and Example 5 was exposed by electron beam lithography (e-beam lithography; EBL) (Germany, Pioneer Two, Raith GmbH), and the voltage was selected to be 30kV, and the aperture diaphragm was selected to be 10mm. The silicon wafer after exposure was immediately developed in toluene for 20s and dried with nitrogen. The developer can also be selected from cyclopentanone, ethyl lactate, ethyl acetate propylene glycol encrypted acetate, propylene glycol methyl ether, etc., and the design line width is less than 50nm.
[0123] The above lithographic patterns were characterized using the scanning electron microscope imaging function of the electron beam lithography system, such as Figure 8 , 10 As shown in Figures 11, the minimum line width dimension that can be obtained in Comparative Example 2 is 36nm, and the line width period (the spacing between adjacent lines) is 100nm. The fluorine-containing oxygen cluster photoresist in Example 5 can achieve a minimum line width dimension of 22nm under the condition of a line width period of 90nm, and can also achieve a line width dimension of 27nm under the condition of 90nm. The photoresist containing fluorine aromatic acid ligand oxygen cluster can achieve a pattern with a lower line width dimension under a smaller line width period, and the pattern quality is good. It is proved that the fluorine-containing aromatic acid ligand improves the imaging quality of the zirconium oxide nanoparticle photoresist and has a more excellent lithography performance.
[0124] Test Example 5
[0125] In order to prove that fluorine-containing aromatic acid ligand can improve the low reactivity problem that fluorine-free aromatic acid ligand brings, use electron beam lithography (e-beam lithography; EBL) (Germany, Pioneer Two, Raith GmbH) to carry out line exposure to the photoresist film in comparative example 4 and embodiment 5, voltage is selected 30kV, and aperture diaphragm is selected 10mm. The silicon wafer after exposure is developed in toluene for 20s immediately, and dries up with nitrogen. Developer can also be selected cyclopentanone, ethyl lactate, ethyl acetate propylene glycol encryption acetate, propylene glycol methyl ether etc., and the design line width is below 50nm.
[0126] The above lithographic patterns were characterized using the scanning electron microscope imaging function of the electron beam lithography system, such as Fig. 9 and Fig.10 As shown in the figure, when the pattern line width of the metal oxide clusters of the two ligands is 27nm and the line width period is 90nm, the exposure dose required for the zirconium metal oxide cluster photoresist without fluorine aromatic acid ligand is 940μC / cm 2 , the exposure dose required for fluorinated aromatic acid ligands is 430μC / cm 2The exposure dose required for the fluorine-containing ligand is greatly reduced, which proves that the fluorine-containing aromatic acid ligand can improve the low reactivity problem brought by the fluorine-free aromatic acid ligand and improve the sensitivity of the fluorine-free aromatic ligand metal oxygen cluster.
[0127] Test Example 6
[0128] In order to prove the influence of the selection of the same fluorine-containing aromatic acid ligand compound ratio on the photolithographic pattern, use electron beam lithography (e-beam lithography; EBL) (Germany, Pioneer Two, Raith GmbH) to carry out line exposure to the photoresist film in Example 5 and Example 6, the voltage is selected to be 30kV, and the aperture diaphragm is selected to be 10mm. The silicon wafer after exposure is developed in toluene for 20s immediately and blown dry with nitrogen. The developer can also be selected from cyclopentanone, ethyl lactate, ethyl acetate propylene glycol encrypted acetate, propylene glycol methyl ether, etc., and the design line width is below 50nm.
[0129] The above lithographic patterns were characterized using the scanning electron microscope imaging function of the electron beam lithography system, such as Fig.10 and Fig.12 As shown, compared with Example 5, Example 6 requires a higher exposure dose to obtain straight lines of the same line width under electron beam exposure, has a lower sensitivity, and has a worse pattern quality. This proves that the selection of the same fluorine-containing aromatic acid ligand compound ratio has a greater impact on the lithographic pattern.
[0130] Test Example 7
[0131] In order to prove the influence of the ligand type of fluorinated aromatic acid ligand compound on the photolithographic pattern, the photoresist film in Example 5 and Example 7 was exposed by electron beam lithography (e-beam lithography; EBL) (Germany, Pioneer Two, Raith GmbH), and the voltage was selected to be 30 kV, and the aperture diaphragm was selected to be 10 mm. The silicon wafer after exposure was developed in toluene for 20 s immediately and dried with nitrogen. The developer can also be selected from cyclopentanone, ethyl lactate, ethyl acetate propylene glycol methyl ether acetate, propylene glycol methyl ether, etc., and the design line width is below 50 nm.
[0132] The above lithographic patterns were characterized using the scanning electron microscope imaging function of the electron beam lithography system, such as Fig.10 and Fig.13 As shown, compared with Example 5, Example 7 requires a lower exposure dose and higher sensitivity to obtain a straight line with the same line width under electron beam exposure, but the quality of the obtained pattern is worse. This proves that the selection of the same fluorine-containing aromatic acid ligand compound has a greater impact on the lithographic pattern.
Claims
1. A zirconium metal oxide nanocluster photoresist material modified by a fluorinated aromatic acid ligand, characterized in that: The general structural formula is Zr6O4(OH)4(MAA) x (L) 12-x , wherein x is 0-11, MAA is a methacrylic acid ligand, and L is a fluorine-containing aromatic acid ligand.
2. The zirconium metal oxide nanocluster photoresist material modified by fluorine-containing aromatic acid ligands according to claim 1, characterized in that: Fluorinated aromatic acid ligands are ligands formed by one or two of the following coordination compounds:
3. The zirconium metal oxide nanocluster photoresist material modified by fluorine-containing aromatic acid ligands according to claim 1, characterized in that: The value of x is 7-11.
4. A method for preparing a zirconium metal oxide nanocluster photoresist material modified by a fluorine-containing aromatic acid ligand as claimed in any one of claims 1 to 3, comprising the steps of: Zr6O4(OH)4(MAA) 12 The solution is mixed with a fluorine-containing aromatic acid ligand compound solution, and after reaction, rotary evaporation and drying, a zirconium metal oxide nanocluster photoresist material modified with a fluorine-containing aromatic acid ligand is obtained.
5. The method for preparing the zirconium metal oxide nanocluster photoresist material modified by fluorine-containing aromatic acid ligand according to claim 4, characterized in that: Includes one or more of the following conditions: i. Zr6O4(OH)4(MAA) 12 The solvent used in the solution is one or a combination of two or more of propylene glycol methyl ether, propylene glycol methyl ether acetate, ethyl lactate, acetone, methanol, ethanol, cyclohexanone, cyclopentanone, tetrahydrofuran, chloroform, n-butanol, dichloromethane or toluene; Zr6O4(OH)4(MAA) 12 The concentration of the solution is 0.01-1 mol / L; ii. The solvent used for the fluorinated aromatic acid ligand compound solution is one or a combination of two or more of propylene glycol methyl ether, propylene glycol methyl ether acetate, ethyl lactate, acetone, methanol, ethanol, cyclohexanone, cyclopentanone, tetrahydrofuran, chloroform, n-butanol, dichloromethane or toluene; the concentration of the fluorinated aromatic acid ligand compound solution is 0.01-1 mol / L; iii. Zr6O4(OH)4(MAA) 12 The molar ratio of the fluorine-containing aromatic acid ligand compound is 1:1-5, preferably 1:3-4.2, and more preferably 1:3; iv. The reaction temperature is room temperature, the reaction time is 5-15 min, and the reaction is carried out under stirring; v. The rotary evaporation temperature is 35-45°C, and the rotary evaporation time is 10-20 minutes; the drying is vacuum drying at room temperature.
6. The method for preparing the zirconium metal oxide nanocluster photoresist material modified by fluorine-containing aromatic acid ligands according to claim 4, characterized in that: The fluorine-containing aromatic acid ligand compound is selected from one or two of the following:
7. The method for preparing the zirconium metal oxide nanocluster photoresist material modified by fluorine-containing aromatic acid ligands according to claim 4, characterized in that: Zr6O4(OH)4(MAA) 12 The preparation method comprises the steps of: mixing the n-propanol solution of zirconium n-propoxide and methacrylic acid uniformly, reacting, standing for crystallization, separating, and drying to obtain Zr6O4(OH)4(MAA) 12 ; Preferably, the concentration of the zirconium n-propoxide n-propanol solution is 60-80wt%; the molar ratio of zirconium n-propoxide to methacrylic acid is 0.1-0.5:1; the reaction temperature is 60-80°C, the reaction time is 15-20h, and the reaction is carried out under stirring; the crystallization temperature is room temperature, and the crystallization time is 1-3 days.
8. A photoresist composition, characterized in that The composition comprises the following components by weight: 1-3 parts of solvent, 0.01-0.5 parts of zirconium metal oxide nanocluster photoresist material modified by fluorine-containing aromatic acid ligand, and 0.005-0.05 parts of photoacid generator; Preferably, the solvent is selected from one or a combination of two or more of propylene glycol methyl ether, propylene glycol methyl ether acetate, ethyl lactate, acetone, methanol, ethanol, cyclohexanone, cyclopentanone, tetrahydrofuran, chloroform, n-butanol, dichloromethane, butyl acetate, n-hexane, N-methylpyrrolidone, carbon tetrachloride, γ-butyrolactone, ethylene glycol ethyl ether, isopropanol or toluene; Preferably, the photoacid generator is selected from 2-(2-(((propylsulfonyl)oxy)imino)thiophene-3(2H)-ylidene)-2-(o-tolyl)acetonitrile (acid generator PAG 103), 2-(2-(((octylsulfonyl)oxy)imino)thiophene-3(2H)-ylidene)-2-(o-tolyl)acetonitrile (acid generator PAG 108), N-hydroxynaphthaleneimide trifluoromethanesulfonic acid, N-hydroxysulfonic acid succinimide or N-hydroxyphthalimide p-toluenesulfonate, or a combination of two or more thereof.
9. The method for preparing the photoresist composition according to claim 8, comprising the steps of: fully dispersing the zirconium metal oxide nanocluster photoresist material modified by fluorine-containing aromatic acid ligands and a photoacid generator in a solvent to obtain the photoresist composition.
10. Use of the zirconium metal oxide nanocluster photoresist material modified with fluorine-containing aromatic acid ligands according to any one of claims 1 to 3 or the photoresist composition according to claim 8 in photolithography technology.
Citation Information
Patent Citations
Photoresist composition and method of forming thin film pattern and array substrate using same
CN111766762A
Photoresist composition, method of forming photolithographic pattern using same, and use thereof
CN111948904A
Photoresist and photoresist patterning method
CN116774522A
Ultraviolet photoresist, and ultraviolet photoresist patterning method and use
WO2023246243A1
Cited By
Nanometer luminescent material and application thereof in photoresist
CN121518133A
Photosensitive nanocrystal material and preparation method thereof
CN121704127A
A photosensitive nanocrystal material and a preparation method thereof
CN121704127B